Max Scheler und Ronald De Sousa über Werte und Gefühle - Moser, Susanne (Labyrinth, 2025)
The aim of this paper is to reconsider Max Scheler's philosophy of values in the light of the renewed discussion of axiological issues in contemporary emotion research. In this context, connections are drawn with Ronald de Sousa, who, like Scheler, seeks to demonstrate the relationship between emotions and values. While Scheler assumes an immediate feeling of value, De Sousa conceptualizes value perception as the apprehension of value properties in analogy to sensory perception. Based on De Sousa's concept of key scenarios and Scheler's assumption of a historically evolved ethos, this paper further analyzes the social and cultural aspects of value perception and the possibility of an objective hierarchy of values.